Discussion of “Flight to Quality in International Markets: Investors’ Demand for Financial Reporting Quality during Political Uncertainty Events” - Hales, Jeffrey (Contemporary Accounting Research, 2018)
Abstract In this paper, I provide a summary and discussion of Chen, Hope, Li, and Wang (2018). In my discussion, I summarize their main findings and focus on key conceptual aspects of their research design. I also comment more broadly on financial reporting quality. Throughout my discussion, I offer a number of specific opportunities to extend this line of research.